2016
DOI: 10.1007/s11356-016-7779-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of indigenous probiotic Lactobacillus strains to reduce cadmium bioaccessibility - An in vitro digestion model

Abstract: The toxic heavy metal cadmium (Cd) appears as one of the major global threats to human and animal health. Human being and aquatic life are exposed to Cd by breathing, eating, or drinking when industrial effluents released into environment. The study was aimed to identify cadmium-binding Lactobacillus strain to reduce its bioaccessibility in in vitro digestion model. In this context, forty-eight lactobacilli strains isolated and characterized from fermented dairy products and human origin were screened for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…; Kumar et al . ). The results from this study show that binding conditions of our strains to cadmium and lead toxicities is due to the freshly cultured nature of the strains.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…; Kumar et al . ). The results from this study show that binding conditions of our strains to cadmium and lead toxicities is due to the freshly cultured nature of the strains.…”
Section: Resultsmentioning
confidence: 97%
“…; Kumar et al . ). Cd and Pb exposure affects delicate part of human body, which causes various toxic disorders including skeletal and cardiovascular dysfunctions (Bhakta et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, sterilization might do damage to physical structure of cell wall, which obviously decreases binding abilities of dead probiotics (Schut, Zauner, Hampel, König, & Claus, ). Several other reports revealed that some probiotic strains belonging to L. plantarum could bind to heavy metals possibly by forming Lactobacilli ‐Cd complex or altering cell components of membranes (Kumar, Kumar, Panwar, & Ram, ; Tong et al, ).…”
Section: Antioxidative and Immune Regulatory Effects Of Probiotics Unmentioning
confidence: 99%